Pengaruh Desentralisasi Fiskal, Investasi dan Tingkat Partisipasi Angkatan Kerja (TPAK) Terhadap Pertumbuhan Ekonomi : (Studi Kasus di Prov. Jawa Tengah Periode 2017-2020) - Utomo, Widhea Indira; Tambunan , Maria R.U.D (Owner : Riset dan Jurnal Akuntansi, 2024)
This Research aims to determine the effect of fiscal decentralization, investment and labor force participation rate on the economic growth of districts or cities in one of the largest provinces on java. This analysis consists of several variables including Investment, labor force participation rate and fiscal decentralization that uses income and expenditure indicators. This study also uses Gross Regional Domestic Product (GRDP) indicators at constant prices for economic growth with total of observations are 140 data from 35 district or cities in Central Java Province for the 2017-2020 period with complete data ownership. The data that used in this study were collected and processed using multiple linear analysis methods to determine simultaneously and particially between fiscal decentralization, investment, labor force participation and economic growth. The research results show that Fiscal Decentralization and Investment have proven to significantly increase economic growth in the Province of Central Java. However, the Labor Force Participation Rate (TPAK) in Central Java Province does not have a significant effect on the economic growth. Regional Income and Regional Expenditure that are well managed will have a positive impact on the economic growth of each region. This can be optimized by taking advantage of current technological developments and demographic bonuses where there is a balance in overcoming good governance, then this will create productivity which can have an impact on economic that more effective and efficient.